Analisis Keselamatan Kerja pada Proses Produksi Pembuatan Kaso Kayu Menggunakan Metode Job Safety Analysis (JSA) - Muhamad Idham Alfaridi; Herly Adam; Danda Nuriansyah; Budiharjo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the level of occupational safety of workers during the wooden rafter manufacturing process at PT. Selamat Megah Putra, and for this purpose the Job Safety Analysis method will be used. The wood processing industry faces a high risk of workplace accidents due to the use of machinery and a high level of manual work. The JSA method helps identify potential hazards, determine their level of risk, and suggest ways to control those risks. Data was collected by directly observing the work environment and speaking with 28 people involved in the production process. The findings indicate that the main hazards faced by workers include inhaling wood dust, loud noise from machinery, wood chips hitting workers, and ergonomic issues such as back pain and the risk of being struck by falling wood. It is recommended to use personal protective equipment, follow safe work procedures, and regularly inspect machinery. The use of Job Safety Analysis has been proven effective in helping workers be more alert and reducing the risk of workplace accidents.